The Effectiveness of STEM Integrated Problem-Based Learning in Enhancing Student Science Literacy on Temperature and Heat Materials - Annisa Sholihah; Syahmani Syahmani; Suyidno Suyidno (Universitas Lambung Mangkurat, 2023)
Science literacy is a key factor in overcoming real-life problems, but it needs to be adequately trained in schools. Therefore, this study aims to analyze the effectiveness of STEM-integrated problem-based learning (STEM-PBL) in enhancing students' science literacy skills. This research is part of research and development with the ADDIE model in the implementation and evaluation stages. The implementation test used a one-group pre-test and post-test design on 58 students divided into two groups. The data collection instruments were science literacy tests and an interview questionnaire. The results showed that: (1) paired t-test results showed that there was a significant increase in students' science literacy skills in both groups; (2) independent t-test results showed that there was no significant difference in the average N-gain score of science literacy in both groups; and (3) n-gain test results for science literacy showed an increase in science literacy in both groups in high criteria. Thus, STEM-PBL is effective in enhancing students' science literacy. STEM-PBL can be the leading solution to realizing the science literacy movement in schools.